Method for improving diffusion performance of chloride ions on single-layer Ta2N by adopting biaxial strain
By applying dual-axis strain to the single-layer TA2N, especially the degree of double-axis strain is -4 %, it optimizes its structure and mechanical properties, solve the problem of poor diffusion performance of chloride ions on the single layer TA2N, and realizes the chloride ionic ionic ions The optimal diffusion performance and good thermal stability.
Patent Information
- Application Number
- CN202411459223.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The diffusion performance of chloride ions on a single layer of Ta2N is poor, which limits the rate performance of chloride ion batteries.
By applying dual-axis strain to the single-layer TA2N, especially the degree of dual-axis strain is -4 % to optimize its structure and mechanical properties, which significantly reduces the degradation of chloride.
A significant reduction of the diffusion energy barrier on the single -layer TA2N, from 0.59EV to 0.17EV, improved the diffusion performance of chloride ions, and maintains good thermal stability at 300K and 500K.
Smart Images

Figure CN119380892A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of computational materials science, and in particular relates to a method for improving the diffusion performance of chloride ions on a single-layer Ta2N by using biaxial strain. Background Art
[0002] With the continuous exploitation and utilization of fossil fuels, mankind is facing serious energy crisis and environmental pollution problems. Energy conversion and storage technology has become a key means to solve this problem. Among them, chloride ion batteries have the advantages of low cost, high theoretical energy density and high safety, and have broad application prospects. However, their poor rate performance seriously restricts the further development of chloride ion batteries. As a typical two-dimensional transition metal nitride, single-layer Ta2N has stable chemical properties, rich reaction active sites and good electronic conductivity, and has become one of the research hotspots in the field of chloride ion batteries. The diffusion performance of chloride ions on single-layer Ta2N still needs to be further improved (the diffusion energy barrier is 0.59eV). The present invention adopts a structural control method with a biaxial strain degree of -4% for single-layer Ta2N, which significantly reduces its chloride ion diffusion energy barrier (the diffusion energy barrier is only 0.17eV), thereby designing a single-layer Ta2N-based chloride ion battery electrode material with excellent rate performance. Summary of the invention
[0003] The object of the present invention is to provide a method for improving the diffusion performance of chloride ions on a monolayer Ta2N by using biaxial strain, so as to make it a chloride ion battery electrode material with excellent chloride ion diffusion performance. The specific implementation method is carried out according to the following steps:
[0004] Step 1: Optimize the structure of the single-layer Ta2N to obtain its stable structure;
[0005] Step 2: Calculate the energy band and state density of the stable Ta2N structure and analyze its electronic structure;
[0006] Step 3: Apply a biaxial strain (ε) of -6% ≤ ε ≤ 6% to the monolayer Ta2N to analyze its mechanical properties;
[0007] Step 4: Calculate the adsorption energy of chloride ions on monolayer Ta2N (after biaxial strain control of -6%≤ε≤6%);
[0008] Step 5: It is confirmed that after the monolayer Ta2N is appropriately biaxially strained (ε=-4%), chloride ions have the best diffusion performance on it;
[0009] Step 6: It is proved that after a suitable biaxial strain (ε = -4%), the monolayer Ta2N has good thermal stability at temperatures of 300K and 500K;
[0010] Aiming at the problem that monolayer Ta2N has poor chloride ion diffusion performance, the present invention proposes a method for improving the diffusion performance of chloride ions on monolayer Ta2N by using biaxial strain, so as to obtain a design scheme and technical route for achieving optimal diffusion performance of chloride ions therein. Firstly, the structure of monolayer Ta2N is optimized to obtain its stable structure; on this basis, the energy band and state density are calculated to prove that it has excellent electronic conductivity; then, different degrees of biaxial strain (ε) (-6%≤ε≤6%) are applied to the monolayer Ta2N, and the structural models of its adsorption of chloride ions are respectively constructed, and the corresponding adsorption energy is calculated. Next, the climbing elastic band (CI-NEB) method was used to analyze and calculate the chloride ion diffusion path and diffusion energy barrier in monolayer Ta2N (after different degrees of biaxial strain, -6%≤ε≤6%), confirming that when a suitable biaxial strain (ε) is applied to Ta2N (ε=-4%), chloride ions have optimal diffusion performance on it (the chloride ion diffusion energy barrier is only 0.17 eV); finally, the ab initio molecular dynamics (AIMD) method was used to prove that Ta2N (after biaxial strain treatment of -4%) has good thermal stability at temperatures of 300K and 500K. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] By describing in detail the embodiments shown in the accompanying drawings, the drawings described below are only some embodiments of the present invention, in which:
[0012] Figure 1 It is an overall flow chart corresponding to a method for improving the diffusion performance of chloride ions on a single layer of Ta2N by using biaxial strain;
[0013] Figure 2 The optimized structure of single-layer Ta2N (top view (a) and side view (b));
[0014] Figure 3 The energy band and state density diagram of single-layer Ta2N;
[0015] Figure 4 (a) is the structure of a single-layer Ta2N after biaxial strain regulation (top view). Figure 4 (b) The variation of Ta-Ta bond length with biaxial strain degree;
[0016] Figure 5 (a) is the structure of a single layer of Ta2N adsorbing a single chloride ion. Figure 5 (b) Chloride ions occupy the top sites of Ta atoms in a single layer of Ta2N (T Ta ), N atom top position (T N ) and vacancies (H) with the variation of the adsorption energy (Ead) with the degree of biaxial strain (ε);
[0017] Figure 6 (a) is the optimal diffusion path of chloride ions in a single layer of Ta2N and a single layer of Ta2N after biaxial strain treatment (ε = -4%), where T N1 and T N2 are two adjacent N atoms at the top, and H1 and H2 are two adjacent vacancies; Figure 6 (b) represents the corresponding chloride ion diffusion energy barrier curve;
[0018] Figure 7 The structure of a single-layer Ta2N (after -4% biaxial strain control) after heat treatment at 300K (a) and 500K (b) and the corresponding total energy change curve with time. DETAILED DESCRIPTION
[0019] This embodiment provides a method for improving the diffusion performance of chloride ions on a single layer of Ta2N by using biaxial strain, comprising the following steps:
[0020] First, the structure of single-layer Ta2N is optimized and calculated to obtain its stable structure; then the energy band and state density of single-layer Ta2N are calculated to analyze its electronic conductivity; then different degrees of biaxial strain (ε is biaxial strain, -6%≤ε≤6%) are applied to the single-layer Ta2N to analyze its mechanical properties; the adsorption structure of chloride ions in the single-layer Ta2N after different biaxial strain regulation (-6%≤ε≤6%) is constructed respectively, and the corresponding adsorption energy is calculated. On this basis, the climbing elastic band (CI-NEB) method is used to find and calculate the optimal diffusion path and diffusion energy barrier of chloride ions in this system. Figure 1 The figure is an overall flow chart corresponding to a method for improving the diffusion performance of chloride ions on a single-layer Ta2N by using biaxial strain.
[0021] Structural optimization calculations were performed on single-layer Ta2N. Figure 2 The structure diagram of the optimized single-layer Ta2N is as follows: the Perdew-Burke-Ernzerh (PBE) method of the generalized gradient approximation (GGA) is used to deal with the exchange correlation energy between electrons; the projected augmented plane wave (PAW) method is used to describe the interaction between electrons and ions; the valence electrons of Ta, N and Cl elements are considered to be 4f 14 5d 3 6s 2 , 1s 2 2s 2 2p 3 and 3s 2 3p 5; The plane wave cutoff energy is set to 500 eV. The Monkhorst-Pack (MP) method is used to set the k-point grid. The 2×2×1 and 4×4×1 k-point grids are used for the structural optimization and electronic structure calculation of the monolayer Ta2N, respectively. The DFT-D2 method is used to describe the van der Waals force between the monolayer Ta2N and the chloride ions. The force convergence accuracy and energy convergence criteria between atoms are set to and 10 -5 In addition, to avoid interlayer interaction, the vacuum layer thickness in the Z direction is set to
[0022] The energy band and state density of single-layer Ta2N are calculated, and its electronic conductivity is analyzed. Figure 3 The energy band and state density diagram of single-layer Ta2N. Figure 3 It can be seen that the energy band and state density of the single-layer Ta2N intersect with its Fermi level, which indicates that it has metallic properties and thus has excellent electronic conductivity, which is conducive to the rapid transmission of electrons in it.
[0023] According to the definition of biaxial strain in formula (2-1), biaxial strain (ε) is applied to the monolayer Ta2N, and the biaxial strain range is: -6% ≤ ε ≤ 6%. The mechanical properties of the material are further analyzed. First, the hexagonal Ta2N is converted into tetragonal Ta2N, and then different degrees of biaxial strain (-6% ≤ ε ≤ 6%) are applied to it (such as Figure 4 (a)), and then the structure of tetragonal Ta2N after biaxial strain is optimized to further clarify the change of Ta-Ta bond length with biaxial strain (ε). The calculation results show that the Ta-Ta bond length shortens with compressive strain and lengthens with compressive strain, and changes linearly (such as Figure 4 (as shown in (b)). In formula (2-1), a0 and b0 are the lattice constants of single-layer Ta2N; a and b are the lattice constants of single-layer Ta2N after biaxial strain.
[0024] After the monolayer Ta2N was subjected to different degrees of biaxial strain (-6% ≤ ε ≤ 6%), the three structures with different chloride ion adsorption were constructed using Materials Studio software (such as Figure 5 (a) shows the three chlorine adsorption sites as follows: the position just above Ta (T Ta ), the position directly above N (T N ), the position directly above the center of the triangle surrounded by three Ta atoms (H). According to formula (2-2), the chloride ion adsorption energy (E) of a single layer of Ta2N (after biaxial strain control to different degrees) is calculated. ad ), the calculation results are as follows Figure 5(b) as shown. In formula (2-2), and are the total energy of the monolayer Ta2N adsorbing chloride ions system and single Ta2N, E Cl is the energy of a single chlorine atom.
[0025] The diffusion energy barrier is one of the key indicators for evaluating whether an electrode material has excellent rate performance, and it is also the innovative core of the present invention. Therefore, based on the monolayer Ta2N chloride ion adsorption system regulated by biaxial strain (-6% ≤ ε ≤ 6%), the climbing elastic band (CI-NEB) method is further used to search for its optimal chloride ion diffusion path and calculate its diffusion energy barrier. At this time, two adjacent optimal adsorption sites of chloride ions in the monolayer Ta2N are selected as the initial and final states of the chloride ion diffusion path, and the relationship between the number of transition states (N) is obtained according to formula (2-3). N=d / Δx (2-3) Where d is the interatomic distance; Δx is the average distance of the transition state; the Δx value here is The number of transition states is 4. Four transition state structures are inserted between the initial state and the final state. These four transition state structures and the initial and final states constitute the chloride ion diffusion path. The four transition state structures are adjusted by using Materials Studio software. On this basis, the chloride ion diffusion path is optimized and calculated, and the corresponding chloride ion diffusion energy barriers are compared.
[0026] After completing the transition state optimization calculation, the output file of the diffusion energy barrier is processed, and different chloride ion diffusion paths are considered to obtain the chloride ion diffusion path and diffusion energy barrier of the monolayer Ta2N after different biaxial strains (-6%≤ε≤6%). Since the optimal adsorption site of chloride ions on the monolayer Ta2N is closely related to the degree of biaxial strain, there are different chloride ion diffusion paths in the monolayer Ta2N after different degrees of biaxial strain control: when the biaxial strain (ε) is at -6%≤ε≤-3%, the chloride ions are from the top position of the N atom (T N ) passes through the vacancy (H) and reaches the top position of the adjacent N atom (T N )(T N →H→T N ); When the biaxial strain (ε) is -2%≤ε≤6%, the chloride ions pass from the vacancy (H) through T N position, reaches the adjacent empty position (H)(T H →T N →T H), when monolayer Ta2N is subjected to appropriate biaxial strain (-4%), chloride ions have the lowest diffusion energy barrier (0.17 eV) on it; therefore, it is confirmed that applying appropriate biaxial strain to monolayer Ta2N can significantly improve its chloride ion diffusion performance.
[0027] The effects of two different biaxial strain control conditions (ε = -4% and ε = 0%) on the diffusion path and diffusion energy barrier of chloride ions in monolayer Ta2N are further compared. The calculated results are as follows: Figure 6 (a) and Figure 6 (b). Figure 6 (b) It can be seen that after the monolayer Ta2N is subjected to appropriate biaxial strain treatment (ε = -4%), the diffusion barrier of chloride ions on it is much smaller than that on the monolayer Ta2N (ε = 0%) (0.17eV vs. 0.59eV). Therefore, biaxial strain control is an effective method to significantly improve the diffusion performance of chloride ions on monolayer Ta2N.
[0028] In addition, thermal stability is also one of the important indicators for measuring the performance of electrode materials. Therefore, the ab initio molecular dynamics (AIMD) method was used to study the thermal stability of single-layer Ta2N at 300K and 500K after optimal biaxial strain (ε = -4%) treatment, and the structures after heat treatment at this temperature were obtained, and the change law of its total energy over time was listed. The results are as follows Figure 7 (a) and 7(b). Figure 7 It can be seen from (a) and 7(b) that after the single-layer Ta2N is heat-treated (temperatures are 300K and 500K respectively), its structure does not undergo obvious distortion and it can always maintain a stable distribution over time, which indicates that Ta2N has good thermal stability after the optimal biaxial strain (ε=-4%).
[0029] Finally, it is necessary to explain here that the above-mentioned specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above-mentioned contents of the present invention belong to the protection scope of the present invention.
Claims
1. A method for improving the diffusion performance of chloride ions on a monolayer Ta2N by using biaxial strain, characterized in that: The method comprises the following steps: Step 1: Optimize the structure of the single-layer Ta2N to obtain its stable structure; Step 2: Calculate the energy band and state density of the stable Ta2N structure and analyze its electronic structure; Step 3: Apply a biaxial strain (ε) of -6% ≤ ε ≤ 6% to the monolayer Ta2N to analyze its mechanical properties; Step 4: Analyze the most stable structure of the chloride ion adsorption system of the monolayer Ta2N after biaxial strain, and calculate its corresponding adsorption energy; Step 5: The climbing elastic band (CI-NEB) method was used to search for the optimal diffusion path of chloride ions on monolayer Ta2N (after different biaxial strain control treatments). It was found that when the monolayer Ta2N was treated with appropriate biaxial strain (ε) (ε = -4%), chloride ions had the best diffusion performance on it; Step 6: The thermal stability of Ta2N treated with biaxial strain (ε) (ε = -4%) at 300K and 500K was studied by ab initio molecular dynamics (AIMD) method.
2. The method of improving the diffusion performance of chloride ions on a single layer of Ta2N by using biaxial strain according to claim 1, characterized in that: In the step 1, the structure of Ta2N is optimized to obtain its most stable structure.
3. The method of improving the diffusion performance of chloride ions on a single layer of Ta2N by using biaxial strain according to claim 1, characterized in that: In step 2, the energy band and state density of Ta2N are calculated to analyze its electronic structure; the specific steps are as follows: Step 2.1: Perform a static self-consistent calculation on the stable Ta2N structure using a Monkhorst-Pack (MP) type 4×4×1 Brillouin zone k-point grid. Step 2.2: The output file obtained from the static self-consistent calculation in step 2.1 is used for the energy band and state density calculation of Ta2N.
4. The method of improving the diffusion performance of chloride ions on a single layer of Ta2N by using biaxial strain according to claim 1, characterized in that: In step 3, biaxial strain (ε) is defined according to formula (1-1), biaxial strain (ε) is applied to Ta2N, and the mechanical properties of the single-layer Ta2N are analyzed; the specific steps are as follows: In formula (1-1), a0 and b0 are the lattice constants of single-layer Ta2N; a and b are the lattice constants of single-layer Ta2N after biaxial strain. Step 3.1: According to step 1, hexagonal Ta2N is converted into tetragonal Ta2N, and then different degrees of biaxial strain (-6%≤ε≤6%) are applied to the tetragonal Ta2N. Step 3.2: Structural optimization of tetragonal Ta2N after biaxial strain was applied in step 3.1, and the bond length was measured.
5. The method of improving the diffusion performance of chloride ions on a single layer of Ta2N by using biaxial strain according to claim 1, characterized in that: In step 4, based on the structure of the chloride ion adsorption system of monolayer Ta2N (after biaxial strain control to different degrees), the corresponding chloride ion adsorption energy (E) is calculated according to formula (1-2). ad ). In formula (1-2), and are the total energy before and after the monolayer Ta2N adsorbs chloride ions, E Cl is the energy of a single chlorine atom.
6. The method of improving the diffusion performance of chloride ions on a single layer of Ta2N by using biaxial strain according to claim 1, characterized in that: In step 5, the optimal diffusion path of chloride ions in the monolayer Ta2N and its biaxial strain system is searched by using the climbing elastic band (CI-NEB) method; the specific steps are as follows: Step 5.1: Obtain the most stable adsorption site of chloride ions on the monolayer Ta2N in step 4, and continue to search for its adjacent equivalent chloride ion adsorption site. Step 5.2: Two adjacent equivalent chloride ion adsorption sites are set as the initial state and final state of the chloride ion diffusion path, and the distance between them is measured; then, based on the relationship between this distance and the transition state, the number of inserted transition states is obtained, thereby designing the diffusion path of chloride ions on a monolayer Ta2N (after biaxial strain (ε) treatment, -6% ≤ ε ≤ 6%). Step 5.3: Use the climbing elastic band (CI-NEB) method to optimize the diffusion path of chloride ions on Ta2N (after biaxial strain (ε) treatment, -6% ≤ ε ≤ 6%) and obtain its corresponding chloride ion diffusion energy barrier.
7. The method of improving the diffusion performance of chloride ions on a single layer of Ta2N by using biaxial strain according to claim 1, characterized in that: In step 6, the ab initio molecular dynamics (AIMD) method is used to prove that Ta2N has good thermal stability at temperatures of 300K and 500K after biaxial strain treatment (ε=-4%).
Citation Information
Patent Citations
System and method for testing diffusion performance of chloride ions in concrete under action of biaxial pressure
CN109883926A
Research method for regulating graphene interlayer phonon friction by applying strain
CN115753469A
Boron-ene metal grid material and screening method and application thereof
CN115862787A
Method for regulating and controlling LaOCl chlorine storage performance from atomic scale based on Ga doping
CN118098446A
Method for improving photocatalytic performance of single-layer gase
WO2024036799A1